2020
DOI: 10.1186/s12879-020-05047-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of IL-1ra was associated with the treatment of latent tuberculosis infection in a Chinese population

Abstract: Background Dynamically changed levels of serum cytokines might predict the development of active TB from latent tuberculosis infection (LTBI) and monitor preventive treatment effectiveness. The aim of the study was to identify potential serum cytokines associated with LTBI treatment which might predict active disease development in a Chinese population. Methods Based on a randomized controlled trial aiming to explore short-course regimens for LTBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…A prospective study by Clifford et al (2017) observed a statistically significant decline in IL-1ra (CFP-10, ESAT-6, PPD), IL-2 (CFP-10, ESAT-6), and IP-10 (CFP-10, ESAT-6) responses after treatment with INH in participants with LTBI. Our previous study in which samples from LTBI participants were unstimulated with mycobacteriaspecific antigen also reported a decrease in IL-1ra responses after treatment and additionally reported that serum IL-1ra was statistically higher among those who developed active disease during follow-up compared with those who stayed healthy (Zhang et al, 2020). A similar finding was observed in our current study, which found the level of IL-1ra decline after preventive treatment for LTBI, suggesting the possibility that it might be used for real-time treatment effect monitoring.…”
Section: Discussionmentioning
confidence: 80%
“…A prospective study by Clifford et al (2017) observed a statistically significant decline in IL-1ra (CFP-10, ESAT-6, PPD), IL-2 (CFP-10, ESAT-6), and IP-10 (CFP-10, ESAT-6) responses after treatment with INH in participants with LTBI. Our previous study in which samples from LTBI participants were unstimulated with mycobacteriaspecific antigen also reported a decrease in IL-1ra responses after treatment and additionally reported that serum IL-1ra was statistically higher among those who developed active disease during follow-up compared with those who stayed healthy (Zhang et al, 2020). A similar finding was observed in our current study, which found the level of IL-1ra decline after preventive treatment for LTBI, suggesting the possibility that it might be used for real-time treatment effect monitoring.…”
Section: Discussionmentioning
confidence: 80%
“…Of the excluded 105 articles which underwent full-text screening, 59 were excluded due to no information on TB preventive treatment, 18 due to mathematics modeling studies, 9 due to no serial data on TB preventive treatment monitoring, 5 due to no biomarkers being tested, 10 due to no data on treatment monitoring, 3 due to the required data being unavailable and 1 due to a sample < 10. Finally, 11 studies were eligible for data extraction and quantitative analysis [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and are listed in Supplementary Table S5 .…”
Section: Resultsmentioning
confidence: 99%
“…The publication of the studies occurred between 2006 and 2022, and the sample size varied from 11 to 2618. Six studies were conducted in Asia [ 33 , 34 , 35 , 36 , 37 , 38 ], three in Europe and two in Africa [ 39 , 40 , 41 , 42 , 43 ]. Six studies were from high TB burden countries [ 33 , 34 , 37 , 38 , 39 , 40 ], two from middle TB burden countries [ 35 , 36 ] and three from low TB burden countries [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been described that IL-37 suppresses activation, proliferation, and cytokine production through down-regulation of nuclear factor-kappa B (NF-κB), and that it inhibits macrophage polarization into the M1 subtype (Zhou et al, 2020). However, this immunomodulatory effect is not observed in A TB patients, who have high circulating levels of IL-37 but not a high expression of its receptors IL-18R and IL-1Ra; this is probably a regulatory mechanism exclusive of the alveolar region (Wawrocki et al, 2019;Moideen et al, 2020;Zhang et al, 2020).…”
Section: Modulation Of the Innate Immunity By Lammentioning
confidence: 99%